Pengaruh Disiplin Belajar dan Lingkungan Belajar Terhadap Tingkat Konsentrasi Belajar Siswa SD N 2 Tahunan - Rahma, Nanda Salsabila; Mufid, Mufid (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2024)
This study examines the issue of suboptimal student concentration during the learning process. The purpose of this research is to identify the influence of learning discipline and learning environment on the concentration of students at SD Negeri 2 Tahunan, Jepara. Learning concentration is a psychological aspect that is often difficult for others to understand besides the individual who is learning. This study uses a quantitative methodology with data collection instruments in the form of questionnaires assessing learning discipline (X1), learning environment (X2), and learning concentration (Y). The number of respondents in this study was 50 students from SD Negeri 2 Tahunan. The data analysis techniques used include multiple linear regression analysis, t-test, F-test, and the coefficient of determination with descriptive statistical analysis. The results of the study indicate that learning discipline and the learning environment significantly influence student concentration, allowing the learning process to proceed according to expectations and learning objectives.